Pelindungan Hukum Terhadap Lahan Pertanian Pangan dari Pengalihan Fungsi untuk Non Pertanian Pangan (Legal Protection of Food Agricultural Land from Conversion to Non-Food Agricultural Land) - Dian Cahyaningrum (Pusat Penelitian Badan Keahlian Setjen DPR RI, 2019)
The conversion of food agricultural land occurs in various region, including Karawang and Tabanan. Consequently, the sustainability of food supply is at stake. This paper examines the importance of legal protection on food agricultural land, the efforts to protect it, the cause of the conversion of food agricultural land, and its solution. This research is a normative and empirical legal research, by using secondary and primary data. Based on the results of the research, the food agricultural land is important to be protected in order to achieve sustainability of food supply, fulfill the people's rights to food, improve farmers' welfare, and preserve the environment. Efforts to protect are implemented preventivly and repressivly. Although protected, the conversion of food agricultural land continues to occur several cause are: the provisions on the protection of food agricultural land have not been followed up, there is demand on land for other purposes, and the farmer’s low income. Several efforts to overcome this by formulating a regulation following up the provision on the protection of food agricultural land, the control of LP2B, and to protect and empower farmers. The central government/regional government must undertake all efforts in the protection of food agricultural land and transform the agricultural sector to be more appealing. AbstrakAlih fungsi lahan pertanian pangan terjadi di berbagai daerah, termasuk Karawang dan Tabanan. Akibatnya ketahanan pangan terancam. Tulisan ini mengkaji pentingnya pelindungan hukum terhadap lahan pertanian pangan, upaya untuk melindunginya, penyebab pengalihan lahan pertanian pangan, dan solusinya. Penelitian ini merupakan penelitian hukum normatif dan empiris, dengan menggunakan data sekunder dan primer. Berdasarkan hasil penelitian, lahan pertanian pangan penting untuk dilindungi agar ketahanan pangan terwujud, hak rakyat atas pangan terpenuhi, meningkatkan kesejahteraan petani, dan menjaga kelestarian lingkungan hidup. Upaya untuk melindungi dilakukan secara preventif dan represif. Meskipun dilindungi, alih fungsi lahan pertanian pangan tetap terjadi. Beberapa penyebabnya: ketentuan pelindungan lahan pertanian pangan belum ditindaklanjuti, desakan kebutuhan lahan untuk kepentingan lain, dan rendahnya penghasilan petani. Beberapa upaya untuk mengatasinya: membuat regulasi teknis mengenai pelindungan lahan pertanian pangan, mengendalikan LP2B, melindungi dan memberdayakan petani. Pemerintah/pemerintah daerah harus melakukan segala upaya untuk melindungi lahan pertanian pangan dan menjadikan sektor pertanian menarik.